Assessing the Impact of Innovative Practices on Customer Experience Satisfaction and Loyalty: A Study on Quick-Service Restaurants in North India - Priyanka Sharma; Parikshat Singh Manhas; Rajani Sarangal (ASEAN Journal on Hospitality and Tourism, 2022)
The primary rationale of this paper is to understand the impact of Innovative practices (IP) on Customer Experience (CE) and Customer Satisfaction (CS) in the Quick Service Restaurant. Further, the study also tends to approach innovative practices (IP) on Customer Loyalty (CL).  The primary data was collected from 462 customers of a QSR belonging to an international brand located in Northern India. The scale development procedure involved Exploratory factor analysis, and confirmatory factor analysis has been used to identify and confirm the factor. Further Structural equation modelling has been used to test the hypothesized relationships. The findings of this study proved that innovative practices positively affect customer experience and Customer satisfaction in quick-service restaurants. The findings further indicated a significant relationship between innovation and customer loyalty. Several studies have been conducted on different aspects of service Innovation. The current study is the first attempt to offer innovative practices influence on Quick Service Restaurants. The paper is helpful for both practitioners and academicians as it would help develop effective marketing and operational strategies for Quick Service Restaurants. Moreover, managers are encouraged to carefully consider innovative practices that will increase the customer experience and the satisfaction toward their service offerings.